Preliminary Report: Osteoarthritis and Rheumatoid Arthritis Synovial Fluid Increased Osteoclastogenesis In Vitro by Monocyte Differentiation Pathway Regulating Cytokines - Luukkonen, Jani; Huhtakangas, Johanna; Palosaari, Sanna; Tuukkanen, Juha; Vuolteenaho, Olli; Lehenkari, Petri (Mediators of Inflammation, 2022)
Background. Rheumatoid arthritis (RA) and osteoarthritis (OA) are common joint diseases associated with changes in local, as well as systemic bone structure and osteoclast function. We investigated how the different soluble inflammatory stimuli in these diseases can affect osteoclastogenesis and bone resorption in vitro. Methods. Human peripheral blood mononuclear cell-derived osteoclasts were cultured on bone slices with serum from treatment-naïve RA patients and healthy controls and with synovial fluid samples acquired from RA and OA patients. The concentrations of 29 different cytokines and related proteins, including RANKL and OPG, were analyzed in the fluids tested. Results. RA serum and synovial fluid increased both osteoclastogenesis and bone resorption. Osteoclastogenesis and activity increased more in the cultures containing OA than RA synovial fluid. The osteoclasts cultured in different culture media exhibited different phenotypes, especially the cells cultured with OA synovial fluid were generally larger and had more nuclei. A general increase in proinflammatory cytokines in RA synovial fluid and serum was found. Surprisingly, OA synovial fluid showed lower levels of osteoclastogenesis inhibiting cytokines, such as IL-4 and IL-10, than RA synovial fluid, which at least partly explains more pronounced osteoclastogenesis. No significant difference was found in RANKL or OPG levels. Conclusion. The proinflammatory stimulus in OA and RA drives the monocyte differentiation towards inflammatory osteoclastogenesis and altered osteoclast phenotype.